In silico Analysis Excavates A Novel Competing Endogenous RNA Subnetwork in Adolescent Idiopathic Scoliosis - Li, Hui-Min; Liu, Yi; Ding, Jing-Yu; Zhang, Renjie; Liu, Xiao-Ying; Shen, Cai-Liang (Frontiers in Medicine, 2020)
Background and Objective: Adolescent idiopathic scoliosis (AIS) is a complex three-dimensional deformity of the spine. Mesenchymal stem cells (MSCs) regulate bone mass homeostasis in AIS, which might be related to the pathogenesis of AIS. However, the mRNA–miRNA–lncRNA network linked to the regulation of the genetic pathogenesis of MSCs remains unknown. Methods: We conducted an exhaustive literature search of PubMed, EMBASE, and the Gene Expression Omnibus database to find differentially expressed genes (DEGs), differentially expressed miRNAs (DE miRNAs), and differentially expressed lncRNAs (DE lncRNAs). Functional enrichment analysis was performed through Enrichr database. Protein–protein interaction (PPI) network was constructed using STRING database, and hub genes were identified by CytoHubba. Potential regulatory miRNAs and lncRNAs of mRNAs were predicted by miRTarBase and RNA22, respectively. Results: We identified 551 upregulated and 476 downregulated genes, 42 upregulated and 12 downregulated miRNAs, and 345 upregulated and 313 downregulated lncRNAs as DEGs, DE miRNAs, and DE lncRNAs, respectively. Functional enrichment analysis revealed that they were significantly enriched in protein deglutamylation and regulation of endoplasmic reticulum unfolded protein response. According to node degree, one upregulated hub gene and eight downregulated hub genes were identified. After drawing the Venn diagrams and matching to Cytoscape, an mRNA–miRNA–lncRNA network linked to the pathogenesis of MSCs in AIS was constructed. Conclusion: We established a novel triple regulatory network of mRNA–miRNA–lncRNA ceRNA, among which all RNAs may be utilized as the pathogenesis biomarker of MSCs in AIS.